Prediction of Women’s Sexual Well-Being Based on Spouses’ Autistic Personality Traits, Alexithymia, and Empathy: The Mediating Role of Loneliness - Ghorbanpour kalateh Molaei, Zhaleh; Saberi, Haeideh; Bashardoost, Simin (Psychology of Woman Journal, 2026)
Objective: This study aimed to predict women’s sexual well-being based on their spouses’ autistic personality traits, alexithymia, and empathy, with loneliness examined as a mediating variable. Methods and Materials: This descriptive–correlational study was conducted among married students from technical faculties of universities in Tehran during the 2025 academic year. A total of 300 heterosexual couples were selected using convenience sampling. Measurement instruments included the Autism-Spectrum Quotient, the Toronto Alexithymia Scale (TAS-20), the Empathy Scale, the UCLA Loneliness Scale, and the Sexual Well-Being Scale. Data analyses were carried out using structural equation modeling (SEM) through SPSS and SmartPLS software. Reliability and validity indices—including Cronbach’s alpha, composite reliability, and average variance extracted (AVE)—indicated strong psychometric adequacy of all constructs. Model fit was evaluated using R², Q², and SRMR indices. Findings: Spouses’ autistic personality traits showed a significant negative effect on women’s sexual well-being (β = −0.378, t = 7.507, p < 0.001). Alexithymia demonstrated a very strong negative relationship with women’s sexual well-being (β = −0.848, t = 7.922, p < 0.001). Conversely, empathy exhibited a significant positive effect on sexual well-being (β = +0.333, t = 7.147, p < 0.001). Loneliness significantly mediated the relationships between emotional traits and sexual well-being (β = −0.418, t = 3.712, p < 0.01). The structural model showed high predictive power, with R² = 0.977 for women’s sexual well-being and acceptable Q² and SRMR values. Conclusion: Emotional and personality traits of male partners—including autistic characteristics, alexithymia, and empathy—play a crucial role in shaping women’s sexual well-being, with loneliness serving as a significant mediating mechanism.